Optimizing ESG Strategy Through ESG Rating Analysis: A Case Study Of PT. X (A State-Owned Enterprise In Indonesia) - Patmanegara, Iqball Dwi Candra; Nainggolan, Yunieta Anny (Journal Integration of Management Studies, 2025)
This study investigates the strategic function of ESG (Environmental, Social, and Governance) Ratings in enhancing sustainability transformation within PT. X is a leading state-owned enterprise in Indonesia's digital sector. Despite maintaining an "A" MSCI ESG Rating from 2020 to 2023, the company lags behind 43% of global peers, raising concerns about ESG maturity and global alignment. Using a qualitative single-case study design, the research draws on in-depth interviews with internal stakeholders and document analysis, examined through thematic and content analysis frameworks. Findings reveal that ESG Ratings serve not merely as compliance instruments but as strategic levers for investor signaling, risk identification, and internal planning. ESG considerations are integrated into KPIs, OKRs, and governance mechanisms, signaling institutionalization of sustainability. However, operational gaps persist, including ESG data infrastructure limitations and inconsistent cross-unit alignment. These insights highlight the evolving role of ESG Ratings as tools for both external market positioning and internal organizational learning. Practically, the study offers guidance for SOEs and emerging-market firms to use ESG Ratings as catalysts for long-term value creation, aligning with national sustainable finance mandates. It recommends investments in ESG data systems, standardized disclosures (e.g., GRI, SASB), and managerial ESG competency-building.